2018
DOI: 10.1037/cap0000159
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health profiles of Canadian psychotherapists: A wake up call on psychotherapists’ mental health.

Abstract: The mental health of psychotherapists represents a key determinant of their ability to deliver optimal psychological services. However, this important topic is seldom the focus of empirical investigations. The objectives of the current study were twofold. First, the study aimed to assess subjective ratings of mental health in a broad sample of Canadian psychotherapists. Second, this study aimed to identify profiles of psychotherapists according to their scores on a series of mental health indicators. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 52 publications
3
30
0
1
Order By: Relevance
“…This confirms our hypothesis. Since mental well-being of psychotherapists represents a key determinant of their ability to deliver high-quality psychological health care ( Salyers et al, 2017 ; La Verdière et al, 2018 ), this illustrates the need to reduce existential stressors due to economic uncertainty, especially for psychotherapists whose income relies solely on psychotherapy. Besides professional policy, stress-management interventions for health care professionals might be further options for psychotherapists who derive all their income from psychotherapy ( Ruotsalainen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms our hypothesis. Since mental well-being of psychotherapists represents a key determinant of their ability to deliver high-quality psychological health care ( Salyers et al, 2017 ; La Verdière et al, 2018 ), this illustrates the need to reduce existential stressors due to economic uncertainty, especially for psychotherapists whose income relies solely on psychotherapy. Besides professional policy, stress-management interventions for health care professionals might be further options for psychotherapists who derive all their income from psychotherapy ( Ruotsalainen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psychotherapists still providing psychotherapy face-to-face during COVID-19 might be especially stressed because of fear of becoming infected with COVID-19. Consequences of these examples might be increased mental burden of psychotherapists, and this distress may negatively impact process and outcome of psychotherapy ( Salyers et al, 2017 ; La Verdière et al, 2018 ). The issue of preventing psychotherapists’ burnout is a central concern in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Person-centered research has started to look at how burnout components combine within employees (e.g., Berjot et al, 2017;Portoghese et al, 2018). However, many previous studies have relied on a combination of burnout components and other variables as profile indicators (work engagement: Mäkikangas et al, 2017; psychological distress and satisfaction with life: Laverdière et al, 2018), making it impossible to isolate the effects of burnout. Among studies focusing solely on burnout, Berjot et al (2017) identified four profiles based on the emotional exhaustion, cynicism, and reduced professional efficacy components (Maslach et al, 2001).…”
Section: Burnout Profilesmentioning
confidence: 99%
“…Past person-centered studies have examined the combined effects of burnout components (Leiter & Maslach, 2016;Pyhältö et al, 2020;Sorkkila et al, 2020). Unfortunately, some of these previous studies have relied on a combination of burnout components and other variables as profile indicators (work engagement: Mäkikangas et al, 2017;work engagement, job satisfaction, and workaholism: Mäkikangas et al, 2015; psychological distress and satisfaction with life: Laverdière et al, 2018), making it impossible to isolate the effects of burnout in the definition of the profiles. In addition, many of these investigations have solely focused on global levels of burnout, making it impossible to consider to unique role played by burnout components.…”
Section: Burnout Profilesmentioning
confidence: 99%